The Influence of the Information Motivation Behavioral Skills Model Approach on Increasing HIV/AIDS Prevention Information - Darlis, Idhar; Gobel, Fatmah Afrianty; Arman; Anunciacion Talosig; Euis Dedeh Komariah (Window of Health : Jurnal Kesehatan, 2024)
The number of HIV/AIDS cases in Indonesia although it tends to fluctuate, data on HIV/AIDS cases in Indonesia continues to increase from year to year. The increase in the spread of HIV/AIDS is certainly very worrying because, in reality, it occurs in all levels of society in almost all provinces, especially within a community group or community. This research aims to analyze the influence of the Information Motivation Behavioral skills model approach on increasing HIV/AIDS prevention information for inmates at Sungguminasa Narcotics Prison. The type of research used is quantitative research with a quasi-experimental pre-post test approach with a control group design. This research was conducted at the Class IIA Sungguminasa Narcotics Prison with a sample size of 60 respondents consisting of 30 for the control and intervention groups. In the intervention group, based on the results of the Wilcoxon statistical test, a P-value of 0.004 < 0.05 was obtained, meaning that there was an influence of the IMB model approach on increasing HIV/AIDS prevention information among inmates at the Sungguminasa Class IIA Narcotics Prison. In the control group, based on the results of the Wilcoxon statistical test, a P-value of 0.132 > 0.05 was obtained, meaning that there was no effect of the IMB model approach on increasing HIV/AIDS prevention information among inmates at the Sungguminasa Class IIA Narcotics Prison. From this research, it can be concluded that the IMB Model influences increasing information for inmates. The IMB model can be an approach that can be applied in the Sungguminasa Class IIA Narcotics Prison.